Odpowiedź:
12.
a)
1/2x - 4 = x - 6 | * 2
x - 4 * 2 = 2(x - 6)
x - 8 = 2x - 12
x - 2x = - 12 + 8
- x = - 4
x = 4
b)
x - 5 = 1/3x + 1 | * 3
3(x - 5) = x + 1 * 3
3x - 15 = x + 3
3x - x = 3 + 15
2x = 18
x = 18/2 = 9
c)
x/4 - 1/4 = 2 | * 4
x - 1 = 2 * 4
x - 1 = 8
x = 8 + 1 = 9
d)
x/5 - 3 = x + 1/5 | * 5
x - 3 * 5 = 5x + 1
x - 15 = 5x + 1
x - 5x = 1 + 15
- 4x = 16
4x = - 16
x = - 16/4 = - 4
e)
5/6(x - 1) = 4 | * 6
5(x - 1) = 4 * 6
5x - 5 = 24
5x = 24 + 5
5x = 29
x = 29/5 = 5 4/5
f)
- 1/2(- x - 6 ) = - x | * 2
- (- x - 6) = - 2x | * (- 1)
-x - 6 = 2x
- x - 2x = 6
- 3x = 6 | * (- 1)
3x = - 6
x = - 6/3 = - 2